-4(x+1)-32=3x-7(x+6)

Simple and best practice solution for -4(x+1)-32=3x-7(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x+1)-32=3x-7(x+6) equation:


Simplifying
-4(x + 1) + -32 = 3x + -7(x + 6)

Reorder the terms:
-4(1 + x) + -32 = 3x + -7(x + 6)
(1 * -4 + x * -4) + -32 = 3x + -7(x + 6)
(-4 + -4x) + -32 = 3x + -7(x + 6)

Reorder the terms:
-4 + -32 + -4x = 3x + -7(x + 6)

Combine like terms: -4 + -32 = -36
-36 + -4x = 3x + -7(x + 6)

Reorder the terms:
-36 + -4x = 3x + -7(6 + x)
-36 + -4x = 3x + (6 * -7 + x * -7)
-36 + -4x = 3x + (-42 + -7x)

Reorder the terms:
-36 + -4x = -42 + 3x + -7x

Combine like terms: 3x + -7x = -4x
-36 + -4x = -42 + -4x

Add '4x' to each side of the equation.
-36 + -4x + 4x = -42 + -4x + 4x

Combine like terms: -4x + 4x = 0
-36 + 0 = -42 + -4x + 4x
-36 = -42 + -4x + 4x

Combine like terms: -4x + 4x = 0
-36 = -42 + 0
-36 = -42

Solving
-36 = -42

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -8-14+5b=11 | | -31-(4x)=-5-5(1+5x) | | (x/2)-6=(x/5)-3 | | x+(12/8)=(3/4)x | | x/15=3/5 | | x+(7/8)=2x-(7/8) | | 3(x-5)+10=5x | | x+5(x+6)+25-12(x-12+5)=25 | | 0.5x+3=x^2 | | x/3+2=8 | | 2(x+4)/5=3x-1 | | 4x+3(x-2)=71 | | 560=(x+10)(x+22)-(x+12)(x) | | X^7-64x=0 | | (2/7)x+(1/7)=-(5/7) | | -7x+4x(3x-5)=-9-6x | | 7x-12-6x=5 | | 7x+14-3x=2(2x+7) | | 7.7r+6=6.7r+6 | | 28-12x=28-14x | | -3x-(7/3)=(29/3) | | 7.7r+6=6.7y+6 | | x^3-x^2-50x+50=0 | | 4n+40=7(-2n+2) | | 2.7x+4.3=12.94 | | 9+5q=13+4q | | (3/4)d-(1/8)=(1/3) | | 20=4/2(6+b) | | x+(x+42826225)=134078221+51604956 | | 2+8y=-32 | | (6/7)x=-18 | | 2-(x+7)=11 |

Equations solver categories